Methods for Estimating the Probability of Clonality in Cell Line Development. Issue 2 (7th January 2020) - Chen, Chun; Le, Kim; Le, Huong; Daris, Kristi; Soice, Neil; Stevens, Jennitte; Goudar, Chetan T.
Abstract: Mammalian cell banks for biopharmaceutical production are usually derived from a single progenitor cell. Different methods to estimate the probability that the cell banks are clonally derived, or the probability of clonality (PoC), associated with various cloning workflows have been reported previously. In this review, a systematic analysis and comparison of the methods used to calculate the PoC are provided. As the single cell deposition and high‐resolution imaging technologies continue to advance and the cloning workflow evolves, an aligned understanding and best practice on estimating the PoC is necessary to compare different cloning workflows adopted across the biopharmaceutical industry and it will help to accelerate regulatory acceptance. Abstract : Ensuring clonally derived mammalian cell banks for biopharmaceutical production is an important regulatory requirement. This review provides mathematical basis for calculating the probability of clonality and compares assumptions previously used in different analysis. An aligned understanding on calculating the probability of clonality based on precise statistics reflecting the real cloning process will facilitate consistent regulatory filing strategy and ensure patient safety.